A Literary and Cultural Stare of the Red Thread Eka Kurniawan - Herdi Sahrasad; Muhammad Ridwan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2019)
This study is a literary and cultural stare of the red thread Eka Kurniawan. As a young writer, Eka Kurniawan successfully spawned three novels that brought her name increasingly known in international literature. His works are also considered capable of inheriting a 'moving' literary tradition, in which the literary notions of socialist realism are echoed. As a results The language of Eka in Beauty, an elegant wound, and the wealth of his imagination provided excitement, like joy when he saw the snow falling for the first time. Ben Anderson even mentioned Eka as Pramoedya's replacement. He also mentioned Eka as the novel writer and the most original short story in Indonesia. Eka claimed to imitate Pram's discipline in making story details. Eka's comment? "I'm still far from Pram," Eka said in response to her comparison with Pramoedya. But it was precisely there that was the challenge for Eka to continue working as Ben Anderson and Pramudya had hoped for him.